(untitled) (Carte Romanze, 2022)
In Jean de Venette’s Histoire des trois Maries he refers to a miracle that happened in Saintes-Maries-de-la-mer in the presence of Robert of Anjou. The article presents the work and its witnesses; reconstructs the historical and literary testimonies linked to the origins of the cult in the Camargue and the innovations proposed by the author; finally it offers an essay of critical edition of two chapters of the text in verse, of its fifteenth-century Latin translation and of the sixteenth-century mise en prose.